2013
DOI: 10.1097/gme.0b013e318269898c
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid concentration in postmenopausal facial skin after topical estradiol and genistein treatment

Abstract: Our data suggest that both treatments may enhance HA concentration in postmenopausal skin but that estrogen produces results that are greater than those produced by isoflavones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…This is in agreement with the findings that estrogen specifically and preferentially promotes HA expression in skin cells [30] and hCG induces HAS2 and HA in murine granular cells during the ovulatory process [31]. Hormone-induced HA secretion of DSCs was dose-associated, peaking at a physiological level observed in human early pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the findings that estrogen specifically and preferentially promotes HA expression in skin cells [30] and hCG induces HAS2 and HA in murine granular cells during the ovulatory process [31]. Hormone-induced HA secretion of DSCs was dose-associated, peaking at a physiological level observed in human early pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…It is reported that long-term application of estrogen increases HA expression in human facial skin [44]. In ovariectomized mice, dermal thickness and decorin expression were found to be reduced [45].…”
Section: Changes In Sulfated Gags and Pgsmentioning
confidence: 98%
“…Phytoestrogens are mainly derived from natural plants and foods. In recent years, phytoestrogens have become a research hotspot in the fight against skin aging (Patriarca et al, ; Sirotkin & Harrath, ; Tuntiyasawasdikul, Limpongsa, Jaipakdee, & Sripanidkulchai, ). Phytoestrogens can increase collagen and hyaluronic acid production and have antioxidant, anti‐inflammatory, and other effects.…”
Section: Discussionmentioning
confidence: 99%
“…Soy isoflavone extract ISO‐1 (containing 12 soy isoflavones) from soybean cake was demonstrated to prevent skin damage caused by UVB exposure. The researchers found that soy isoflavones (daidzin, genistin and glycitin) could inhibit UVB‐induced death of human keratinocytes and reduce the level of desquamation, TEWL, erythema, and epidermal thickness in mouse skin (Huang et al, ; Patriarca et al, ).…”
Section: Effect On Water Contentmentioning
confidence: 99%
See 1 more Smart Citation